A New Multilevel Inverter Topology Based On Cascaded H-Bridge With Reduced Switching Components Using Modified PWM Technique - Suganya A V, Arvin Tony, Brindha Sakthi B (International Journal of Advanced Science and Technology, 2020)
The multilevel inverter has more challenges and attention among the researchers, because it is widely accepted for the DC to AC conversion used for medium and high-power applications. In conventional multilevel converter the number of level increases with the number of power switches. The performance of this multi-stepped output waveform is realized in terms of number of power switches and Total Harmonic Distortion (THD). This paper proposes a nine-level inverter with reduced number of power switches for medium power applications and modified PWM generation. In this proposed system each level of output voltage uses reduced number of switches for conduction by its series and parallel combination. The modified PWM technique yields a low Total Harmonic Distortion (THD). To verify the proposed system, the computer-based simulation model is developed using MATLAB/Simulink.